IMPLEMENTASI MANAJEMEN BERBASIS MADRASAH (MBM) DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI MADRASAH ALIYAH NEGERI 2 LUBUKLINGGAU - Kholai Kholai; Fitriyani Fitriyani; Muhammad Qomarullah (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2020)
Education is a conscious and planned effort in realizing an atmosphere of learning and learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble character, and the skills needed by themselves, the people of the nation and the State. Based on these problems, the formulation of the research problem is: (1) How is the quality of learning in MAN 2 Lubuklinggau (2) How is the implementation of Madrasah Based Management in improving the quality of learning in MAN 2 Lubuklinggau (3) What are the supporting and inhibiting factors that influence the Implementation of Madrasah Based Management in improving the quality of learning at MAN 2 LubuklinggauThis research is a qualitative descriptive research. With the Head of Madrasa as the research subject. In collecting data, the authors use the method of observation, interviews and documentation. Data is collected from the information specified, the results relevant to the problem under study are analyzed quantitatively through the process of data collection, data reduction, data presentation and drawing conclusions.The results of this study indicate that the quality of the learning process in Madrasah Aliyah Negeri 2 Lubuklinggau can be said to be good. This is evident from the teachers who teach in accordance with their respective educational qualifications. With the Implementation of Madrasah-Based Management in improving the quality of learning at MAN 2 Lubuklinggau, it reveals the Management of Madrasas, the performance of Madrasah Heads / teachers, and the role of Community Participation. The implementation of the Madrasah-Based Management Program will be carried out well with the collaboration between Curriculum Management and Teaching Programs, Management of Education Personnel, Student Management, Financial Management and Financing, Management of Educational Facilities and Infrastructure, Management of School and Community Relations, and Management of Special Services.